AB0254 Sonographic and Clinical Characterization of A Prospective Cohort of Patients with Rheumatoid Arthritis in Clinical Remission. Preliminary Results. (10th June 2014) - Ramírez García, J.; Ruíz-Esquide, V.; Celis, R.; Cuervo, A.; Cabrera, S.; Inciarte-Mundo, J.; Sanmartí, R.; Cañete, J.D.
Abstract : Objectives: To analyse clinical and sonographic predictors of clinical flares in patients with rheumatoid arthritis in clinical remission (DAS28<2.6). Methods: Prospective study with 12 months follow-up. Patients diagnosed with rheumatoid arthritis who were in clinical remission (defined as DAS28 <2.6) were included. Clinical, epidemiological, demographic and serological data at baseline and 12 months were analysed. Serum concentrations of several cytokines and angiogenic factors were analysed by ELISA at baseline (RayBiotech). We performed ultrasound scans of both knees and hands (wrists, metacarpophalangeal [MCP], proximal interphalangeal [PIP] flexor and extensor tendons of the hand). Ultrasonography was done by a rheumatologist experienced in musculoskeletal ultrasound using high sensitivity equipment (Acuson Antares®, Siemens AG, Erlangen, Germany) with a 8-12 MHz linear probe. We quantified the presence of synovial hypertrophy (grades 0-3) and power Doppler signal (grades 0-3) in all patients. Results: We included 28 patients in clinical remission (23 females and 5 males with a mean age (SD) of 51.9 (11.9) years and a disease duration of 108.2 (92.6) months). 71.9% of patients were positive for rheumatoid factor and anti-citrulline antibodies. 75% of patients were on at least one DMARD and 39.3% were on biological treatment. 60.7% of patients had power Doppler signal at baseline and 46.4% met criteria for our definition of active synovitis (synovial hypertrophy ≥2 + Power Doppler signal, Ramirez J et al, Arthritis Research and Therapy 2014). After one year of follow-up, 12 patients (42.9%) did not meet criteria for clinical remission. Of these, 9 had Power Doppler signal in the first ultrasound assessment (p=0.034) and 7 met criteria for defined subclinical synovitis by ultrasound (p=0.291). These patients also had higher levels of ESR (p=0.046) and lower TGF- b1 (p=0.082) at baseline. A logistic regression model found that Power Doppler signal at baseline was the main predictor of clinical reactivation at 12 months (OR 6.18). Conclusions: Although an elevated ESR or a low concentration of TGFb1 at baseline seems to be associated with clinical reactivation of patients with RA in remission, Power Doppler signal is the best predictor of disease reactivation at 12 months. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4310